PSIX-2 Feeding 3-nitrooxypropanol reduces methane emissions by feedlot cattle - Da Ros de Araújo, Tiago Luís (J Anim Sci, 2020)
Our objective was to evaluate the effects of feeding 3-nitrooxypropanol (3NOP; Bovaer(®), DSM Nutritional Products) at two doses on methane emissions and performance by feedlot cattle. The experiment was designed as a completely randomized block, in which 138 Nellore bulls (iBW, 360 ± 37.3 kg) were placed in collective pens (9 pens per treatment) and fed a high-concentrate diet (R:C, 11:89) according with the following three treatments: 1) 0ppm 3NOP /day; 2) 100ppm 3NOP/day, or 3) 150ppm 3NOP/day. For performance and DMI assessments the pen was the experimental unit. For methane emission evaluations, CH(4) and DMI were assessed individually in 12 pens (2 bulls/pen, 8 bulls (experimental units)/treatment). Methane emission was measured for 6 consecutive days using the sulfur hexafluoride (SF(6)) tracer technique in two times over the experimental period (d15d -d21) and (105d to 111d), whereby the gross energy (GE) variables were calculated using equations. The individual DMI was measured using the two markers technique (Chromium oxide and indigestible NDF). The data were analyzed using the Mixed procedure of SAS and means comparison were carried out by Tukey’s test. Regardless of the level, dietary supplementation with 3NOP decreased (P < 0.001) methane emissions by 49.7% as expressed as g/d (146.0 vs. ~74 g/d(−1)); by 38.6% when expressed as g/kg ADG (91 vs ~56 g/kg ADG), and by 40.7% when expressed as g/kg DMI (13.5 vs. ~8 g/kg DMI). Likewise, dietary supplementation with 3NOP decreased (P < 0.001) the GE loss as a percentage of the GE intake by 42.4% (4.74 vs ~2.73%). However, feeding 3NOP had no effect on animalsˈ DM intake (~2.43 %BW; P = 0.23), ADG (~1.52 kg/d; P = 0.11) and HCW (~284 kg, P = 0.26). We conclude that Bovaer(®) can be used to effectively reduce methane emission by feedlot cattle without adverse effects on performance.